Estudio de la Calidad del Agua del Río Pita, ubicado dentro del Distrito Metropolitano de Quito en el Periodo 2013-2019. - Ashanka Vargas, Matteo Anthony (2020)
The bodies of water are currently exposed to natural contamination due to landslides, runoffs, cyclones, among others, and to that of anthropic origin, the latter being the cause of the main adverse effects. This research aims to evaluate the water quality of the “Pita River”, located within the Metropolitan District of Quito in the 2013-2019 period. Subsequently, a mathematical model is applied to estimate the water quality in 4 years. The data was obtained through the Metropolitan Network database of water resource monitoring and the application of the ISQA methodology (Simplified Water Quality Index). The results of physicochemical analysis in the period 2013-2019 showed that the water of the “Pita” river presented low concentrations of COD that oscillate between 10.9 mgL-1 in the 2019 year to 14.4 mgl-1 in the 2013 year, the TSS fluctuated between 14, 7 mgl-1 in 2019 to 50 mgL-1 in 2016, the EC ranged from 176.8 uS/cm in 2019 to 197.5 uS/cm in 2018, the temperature ranged from 12.3°C in 2013 to 13.3°C in 2019 and the OD fluctuated from 6.9 mgL-1 in 2016 to 8, 1 mgL-1 in 2018, and quality values were determined between the range 70-90 which classifies the quality of water as good, suitable for human consumption prior to conventional treatments, usable for low-resistance crops and recreational use. On the other hand, it was appreciated that only three months in the entire period showed quality values between 90-100, estimated as a natural state of water of excellent quality, suitable for all uses and does not require treatment for irrigation. Additionally, a predictive mathematical modeling was applied, using the method of decomposition of time series, which through a mathematical equation relates the components of time series as the trend and seasonality, the model showed that the concentrations of COD, TSS and T will decrease over time while the concentrations of OD and EC, will have a minimum increase in the periods 2020-2023, water quality in this period will take values of 70-90, classified as good quality water. According to Ecuadorian regulations (TULSMA), Book VI, Annex 1, Table 6, on water quality criteria for recreational purposes, the parameter OD did not exceed the LMP and according to the quality standards of the United States Environmental Protection Agency (USEPA), the concentrations of Temperature and EC do not exceed the LMP. It is established that the water of the “Pita” River is in optimal conditions of use for recreational activities and human consumption prior to conventional treatments, and good water quality is expected for the four future years.